COMPARATIVE STUDY OF ECG FINDINGS IN SMOKERS AND NON- SMOKERS AMONG PATIENTS IN A TERTIARYCARE HOSPITAL - D.ANJU, B. DEEPIKA, S. BHAVADHARANI, S. HARIPRASADH, K. ARUN, M. JENIFER, R. YAMINI, V. RAMNATH (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Smoking is a major preventable cause of cardiovascular disease world wide, accounting for over 7 million deaths annually. Smoking damages the cardiovascular system, leading to atherosclerosis, cardiac remodelling and increased risk of MI, stroke and arrhythmias. ECG is a non invasive tool for assessing cardiac electrical activity and detecting early signs of cardiovascular diseases. Smoking induce ECG changes, such as QT interval prolongation, ST segment depression and T wave abnormalities have been linked to increased cardiovascular disease. To compare the ECG changes between smokers and non-smokers patients among a tertiary care hospital. The study included 100 patients, both smokers and nonsmokers, aged20 to 65, who visited the MMCHCRI outpatient department. According to the criteria, 61of the volunteers were smokers, and the remaining 39 were nonsmokers with no smoking or alcohol consumption. Following at horough examination, all subjects were asked to refrain from smoking for two hours before the ECG recording. The ECG was recorded in the Department of Cardiology lab at MMCHCRI. The following parameters were valuated: heart rate, p wave, PR interval, and QRS complex..The wave duration was measured in seconds using a bar and pie chart. The analysis shows that smokers the age group of >55 have a higher abnormality in ECG with high COPD cases. ECG changes were significantly more prevalent among smokers, including ST segment abnormalities, T wave inversions, QT prolongation, and arrhythmias. These findings reinforce smoking as a modifiable risk factor for cardiovascular disease. Early ECG screening and smoking cessation can play a crucial role in preventing cardiac complications.